2012
DOI: 10.1021/om3008597
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Studies of the Reaction of Carbon Dioxide with Pincer-Supported Nickel and Palladium Hydrides

Abstract: A series of Ni(II) and Pd(II) hydrides supported by PNP and PCP ligands, including iPr2 PNP (CH3) PdH ( iPr2 PNP (CH3) = N(2-P i Pr 2 -4-MeC 6 H 3 ) 2 ), iPr2 PNP (CH3) NiH, iPr2 PNP (F) PdH ( iPr2 PNP (F) = N(2-P i Pr 2 -4-C 6 H 3 F) 2 ), CyPh PNPPdH ( CyPh PNP = N(2-P(Cy)(Ph)-4-MeC 6 H 3 ) 2 ), tBu2 PCPPdH ( tBu2 PCP = 2,6-C 6 H 3 (CH 2 P t Bu 2 ) 2 ), tBu2 PCPNiH, Cy2 PCPPdH ( Cy2 PCP = 2,6-C 6 H 3 (CH 2 PCy 2 ) 2 ), and Cy2 PCPNiH, were prepared using literature methods. In addition, the new Ni and Pd h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 63 publications
5
101
0
4
Order By: Relevance
“…The 1 H NMR spectrum of 1 in C 6 D 6 shows resonances between δ =7.07 and 0.98 ppm, with a pattern expected for a C 2 v symmetric nickel centre with square‐planar coordination. The formate proton gives rise to a singlet at δ =5.40 ppm, which appears to be shifted to exceptionally high fields compared to other nickel formates; this is probably due to the donation of electron density from the occupied nickel d xy orbital to the formate carbon atom, which leads to a shielding of the formate proton.…”
Section: Figurementioning
confidence: 99%
“…The 1 H NMR spectrum of 1 in C 6 D 6 shows resonances between δ =7.07 and 0.98 ppm, with a pattern expected for a C 2 v symmetric nickel centre with square‐planar coordination. The formate proton gives rise to a singlet at δ =5.40 ppm, which appears to be shifted to exceptionally high fields compared to other nickel formates; this is probably due to the donation of electron density from the occupied nickel d xy orbital to the formate carbon atom, which leads to a shielding of the formate proton.…”
Section: Figurementioning
confidence: 99%
“…The calculated ΔG ‡ values for CO 2 insertion into nickel hydrides with various pincer ligands agree reasonably well with the experimental data. 23 Meanwhile, the comparison between nickel and palladium systems through the computational study suggests the possibility that a judicious selection of ligand could lead to even better reactivity for a nickel hydride than a palladium hydride.…”
Section: ■ Nickel Pocop-pincer Complexesmentioning
confidence: 99%
“…Recently, both our research group7q and Mitton and Turculet7o investigated the insertion of CO 2 into [( Cy PSiP)PdH]8 ( Cy PSiP=Si(Me)(2‐PCy 2 ‐C 6 H 4 ) 2 , in which Cy is cyclohexyl), and demonstrated that a Pd formate was rapidly generated. We were interested in exploring the same reaction with the related complex [( Ph PSiP)PdH] ( Ph PSiP=Si(Me)(2‐PPh 2 ‐C 6 H 4 ) 2 ), which Takaya and Iwasawa proposed to be a crucial intermediate in allene carboxylation 7d.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of hydride source does not appear to be crucial, as when [( Ph PSiP)PdCl] was treated with LiAlH 4 instead of LiEt 3 BH, [( Ph PSiP) 2 Pd 2 ] was observed in the 31 P NMR spectrum. Given that the analogous reaction between [( Cy PSiP)PdCl] and LiEt 3 BH results in the clean formation of [( Cy PSiP)PdH],7q it is probable that the formation of [( Ph PSiP) 2 Pd 2 ] occurs through a transient [( Ph PSiP)PdH] species, although even at low temperature there is no evidence for the formation of this intermediate. Presumably, the relative lack of steric bulk in [( Ph PSiP)PdH] results in bimolecular dimerization, whereas the more sterically protected complex [( Cy PSiP)PdH] is stable 8…”
Section: Methodsmentioning
confidence: 99%